Tobramycin inhalation powder manufactured by improved process in cystic fibrosis: the randomized EDIT trial. (4th June 2013) - Galeva, Ivanka; Konstan, Michael W.; Higgins, Mark; Angyalosi, Gerhild; Brockhaus, Florian; Piggott, Simon; Thomas, Karen; Chuchalin, Alexander G.
Abstract: Background: Tobramycin inhalation powder (TIP) was reported to be effective in two Phase III studies in patients with cystic fibrosis (CF) chronically infected with Pseudomonas aeruginosa ( Pa ). The EDIT study evaluated the efficacy and safety of TIP manufactured by an improved process in CF subjects aged 6–21 years. Methods: CF patients with a forced expiratory volume in 1 second (FEV1 ) ≥25% to ≤80% predicted, positive Pa cultures and inhaled antipseudomonal therapy naïve (or at least for past 4 months) were enrolled into this double-blind, multicenter trial. Patients were randomized to receive TIP or placebo (1:1) twice daily for one treatment cycle (28.5 days on drug, 28 days off drug). The primary endpoint was relative change in FEV1 percentage predicted from baseline to day 29. A pre-specified sensitivity analysis evaluated absolute change in FEV1 % predicted. Other endpoints included Pa sputum density and safety. Results: A total of 62 patients out of a target of 100 (mean age 12.9 years, baseline FEV1 59.2% predicted, Pa sputum density 7.4 log10 colony forming units [CFU] per gram) were randomized. Mean treatment differences (TIP - placebo) were 5.9% ( p = 0.148) and 4.4% ( p < 0.05) for relative and absolute change in FEV1 % predicted respectively. TIP significantly reduced Pa sputum density by −1.2 log10 CFU ( p = 0.002). Treatment with TIP was well tolerated. Conclusions: Relative change in FEV1 % predicted with TIP treatment was in the expected range based on the literature, but did not reach statistical significance versus placebo. Placebo control and use of treatment naïve patients led to significant recruitment challenges and an underpowered study with consequent impact on the generated data. However, significant improvements in other outcomes including absolute change in FEV1 % predicted and reduction in Pa sputum density indicate that TIP is efficacious and well tolerated in CF patients. ClinicalTrials.gov identifier: NCT00918957.